Single-photon-added coherent state-based postselected weak measurement - Yi-Fang Ren; Yusuf Turek (Results in Physics)
We investigated precision measurements in a two-level system coupled to a single-photon-added coherent state (SPACS) under postselected weak measurement. We analyzed strategies for improving measurement precision, including parameter estimation and the signal-to-noise ratio (SNR) in postselected weak measurements, using the photon statistics of SPACS as the meter. Our results demonstrate that SPACS-based postselected weak measurements can outperform conventional measurement schemes in terms of precision. Additionally, we explicitly introduced an alternative weak measurement method, which is commonly applied in dispersive light-atom interactions. Our work presents a novel approach to addressing fundamental issues in quantum precision measurement based on photon statistics, and it provides a method for extracting the photon and phase shifts of radiation fields through the weak values of system observables.